COMPARISON OF TRIGLYCERIDE LEVELS BETWEEN SERUM STORED AT -20°C AND SERUM AT 25°C FOR 2 DAYS AT TOTO KABILA REGIONAL GENERAL HOSPITAL (Journal of Health, Technology and Science (JHTS), 2025)
The pre-analytical phase carries a relatively high risk of error, accounting for 50%-75% of total laboratory errors, including those related to sample storage. In triglyceride testing, storage conditions are crucial as they can affect serum stability . This study compares triglyceride levels between serum samples stored at -20°C and those stored at 25°C for two days at Toto Kabila Regional General Hospital. The study employed a quantitative approach with an analytical observational design, using 16 serum samples from hospital patients. Data were analyzed using the Independent Sample T-test. The results showed that the average triglyceride level in serum stored at -20°C was 131.83 mg/dL, while in serum stored at 25°C it was 188.48 mg/dL. The Independent Sample T-test yielded a significance value of 0.023 (